All visitors welcomed: how universal access supports inclusive activities in protected natural areas - Sears, Maly (Kansas State University, 2024)
Protected natural areas often have a dual mission to conserve both cultural and natural resources while offering recreational and educational opportunities (Alexander 2007). However, individuals with disabilities often face unequal access within natural areas due to various physical, informational, and programmatic barriers (Groulx, Freeman, and Lemieux 2022). While some guidelines for implementing universal design and access in urban spaces exist, there is a lack of knowledge and guidance for applying universal access in protected natural areas alongside additional priorities like conservation and visitor management (Groulx et al. 2021). To fill this knowledge gap, a proposed universal access Guidebook for land managers was developed for use in protected natural areas. Methods used to inform the Guidebook included an analysis of prominent universal design and visitor use guidelines and eight semi-structured interviews with land managers, visitor program directors, and accessibility specialists. The Guidebook incorporates the specific challenges and opportunities identified by the interviewees and provides actionable strategies, considerations, and an integrated planning process to create high quality, inclusive experiences. To demonstrate the application of the Guidebook, a projective design was proposed for Konza Prairie Biological Station, located in the Flint Hills Region of Kansas. The recommendations and design show how the site can provide equitable visitor experiences for all. The findings confirmed that visitor access and management planning in natural areas does not typically consider universal access. Additionally, the findings revealed that opportunities and challenges go beyond the need for adapted universal access guidelines. Fostering collaboration, knowledge sharing, and improving access to resources and funding are also critical to successfully implementing universal access. Research limitations include a limited number of interviewees and a lack of feedback on the proposed Guidebook. Future research should include more interviewees and the guidebook should be reviewed by experts and those with lived experience with disabilities. Overall, the Guidebook encourages land managers to implement universal access in protected natural areas which would allow all people, regardless of ability, to enjoy the beauty of nature.
Keywords: Universal design; Universal access; Protected natural areas; Visitor use management